We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
154
2
avatar+608 

If we write \(\sqrt{2}+\frac{1}{\sqrt{2}} + \sqrt{3} + \frac{1}{\sqrt{3}}\) in the form \(\dfrac{a\sqrt{2} + b\sqrt{3}}{c}\) such that \(a\)\(b\), and \(c\) are positive integers and \(c\) is as small as possible, then what is \(a + b + c\)?

 Sep 23, 2018
 #1
avatar
+1

Simplify the following:
sqrt(2) + 1/sqrt(2) + sqrt(3) + 1/sqrt(3)

Rationalize the denominator. 1/sqrt(2) = 1/sqrt(2)×(2^(1 - 1/2))/(2^(1 - 1/2)) = (2^(1 - 1/2))/2:
sqrt(2) + (2^(1 - 1/2))/2 + sqrt(3) + 1/sqrt(3)

 

Combine powers. (2^(1 - 1/2))/2 = 2^((1 - 1/2) - 1):
sqrt(2) + 2^((1 - 1/2) - 1) + sqrt(3) + 1/sqrt(3)

Put 1 - 1/2 over the common denominator 2. 1 - 1/2 = 2/2 - 1/2:
sqrt(2) + 2^(2/2 - 1/2 - 1) + sqrt(3) + 1/sqrt(3)

2/2 - 1/2 = (2 - 1)/2:
sqrt(2) + 2^((2 - 1)/2 - 1) + sqrt(3) + 1/sqrt(3)

2 - 1 = 1:
sqrt(2) + 2^(1/2 - 1) + sqrt(3) + 1/sqrt(3)

 

Put 1/2 - 1 over the common denominator 2. 1/2 - 1 = 1/2 - 2/2:
sqrt(2) + 2^(1/2 - 2/2) + sqrt(3) + 1/sqrt(3)

1/2 - 2/2 = (1 - 2)/2:
sqrt(2) + 2^((1 - 2)/2) + sqrt(3) + 1/sqrt(3)

1 - 2 = -1:
sqrt(2) + 2^((-1)/2) + sqrt(3) + 1/sqrt(3)

 

Rationalize the denominator. 1/sqrt(2) = 1/sqrt(2)×(sqrt(2))/(sqrt(2)) = (sqrt(2))/2:
sqrt(2) + (sqrt(2))/2 + sqrt(3) + 1/sqrt(3)

Rationalize the denominator. 1/sqrt(3) = 1/sqrt(3)×(sqrt(3))/(sqrt(3)) = (sqrt(3))/3:
sqrt(2) + (sqrt(2))/2 + sqrt(3) + (sqrt(3))/3

 

Put each term in sqrt(2) + (sqrt(2))/2 + sqrt(3) + (sqrt(3))/3 over the common denominator 6: sqrt(2) + (sqrt(2))/2 + sqrt(3) + (sqrt(3))/3 = (6 sqrt(2))/6 + (3 sqrt(2))/6 + (6 sqrt(3))/6 + (2 sqrt(3))/6:
(6 sqrt(2))/6 + (3 sqrt(2))/6 + (6 sqrt(3))/6 + (2 sqrt(3))/6

(6 sqrt(2))/6 + (3 sqrt(2))/6 + (6 sqrt(3))/6 + (2 sqrt(3))/6 = (6 sqrt(2) + 3 sqrt(2) + 6 sqrt(3) + 2 sqrt(3))/6:
(6 sqrt(2) + 3 sqrt(2) + 6 sqrt(3) + 2 sqrt(3))/6

Add like terms. 6 sqrt(2) + 3 sqrt(2) + 6 sqrt(3) + 2 sqrt(3) = 9 sqrt(2) + 8 sqrt(3):

(9 sqrt(2) + 8 sqrt(3))/6 = a =9, b=8, c=6: a + b + c =9 + 8 + 6 = 23

 Sep 24, 2018
edited by Guest  Sep 24, 2018
 #2
avatar+17972 
+2

Here is my hand  scrawled answer:

 

 Sep 24, 2018

14 Online Users

avatar